The expert witness in construction - Horne, Robert; Mullen, John, 1959- (Hoboken, N.J. : Wiley Blackwell, 2013)
The role of the expert witness has long been important in the resolution of construction disputes. The specialist opinion brought by the expert can aid understanding and interpretation of the facts of the dispute, and may be influential in deciding the outcome. The variety of dispute resolution procedures and the requirement for the expert witness to be independent places a heavy burden on the parties to identify and instruct an appropriate expert, and on the expert to ensure they discharge their duty in the correct manner.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Evidence, Expert; Construction industry -- Law and legislation; Construction contracts; LAW -- Military; Construction contracts; Construction industry -- Law and legislation; Evidence, Expert; Electronic books